Brockmire. The complete third season [videorecording (DVD)] - Marable, Maurice; Azaria, Hank, 1964-; Peet, Amanda, 1972-; Williams, Tyrel Jackson (Lionsgate, 2020)
A famous major league baseball announcer has an embarassing meltdown on the air when he finds out that his wife has been unfaithful to him and subsequently tries to redeem himself by calling minor league games in a small town.